Information and communication technology, upgrading of industrial structure and spatial spillover effect - Heyuan Fang; Kashif Iqbal (Scientific Reports)
Abstract Against the backdrop of China’s “dual-carbon” goals and regional coordination strategies, information and communication technology (ICT) is positioned as a critical enabler to resolve efficiency-resource trade-offs and bridge spatial development gaps. This paper investigates the impact of ICT on the industrial structure upgrading (ISU) process using the Spatial Dubin Model (SDM). Based on the panel data of cities in the Yangtze River Delta region of China from 2001 to 2023, the empirical results indicate that ICT has a positive effect on ISU and that there are significant positive spatial spillover effects. Technological innovation and productivity improvement play essential mediating roles during this process. We also find that ICT has a greater impact on the cities in the early stages of industrial upgrading than on those in the developed stages. These findings offer actionable insights for policymakers to leverage ICT’s cross-regional synergies, particularly in emerging economies grappling with imbalanced industrial ecosystems and sustainability constraints.